Static analysis and dynamic steering of time-dependent systems. - Vicario, E. (IEEE Transactions on software engineering)
An enumerative technique is presented which supports reachability and timeliness analysis of time-dependent models. The technique assumes a dense model of time and uses equivalence classes to enable discrete and compact enumeration of the state space. Properties of timed reachability among states are recovered through the analysis of timing constraints embedded within equivalence classes. In particular, algorithms are given to evaluate a tight profile for the set of feasible timings of any untimed run. Runtime refinement of static profiles supports a mixed static/dynamic strategy in the development of a failure avoidance mechanism for dynamic acceptance and a guarantee of hard real-time processes